Technology-Driven Motivation: Quizizz for Reading Comprehension in Vocational School - Krisanti Dhiaz Ayuni; Tri Wahyuni Floriasti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The lack of student motivation in understanding English reading texts at vocational schools remains a major challenge for effective learning. This issue is exacerbated by traditional teaching methods that provide limited active student participation. This study aims to analyze the effect of using Quizizz on students’ reading comprehension motivation among eleventh graders at SMKN 2 Depok, Sleman, Yogyakarta. Employing a quantitative approach with an ex post facto design, the research involved 71 students who had used Quizizz in English reading activities. Data were collected through validated and reliable questionnaires, then analyzed using descriptive statistics, prerequisite tests (normality and linearity), simple regression, and a one-sample t-test. Results revealed an average score of 4.03 for Quizizz use and 3.99 for reading motivation. Normality (p = 0.200) and linearity tests (p = 0.000; p = 0.602) confirmed the data suitability. Regression analysis indicated that Quizizz significantly influenced student motivation (p < 0.000, R² = 0.53). One-sample t-tests further showed both variables scored higher than the moderate value (t = 16.571; t = 14.012; p < 0.000). These findings highlight that Quizizz effectively enhances motivation, fosters engagement, and creates an interactive and enjoyable learning experience, thereby supporting technology-based learning.